2000
DOI: 10.1016/s0168-1702(00)00126-x
|View full text |Cite
|
Sign up to set email alerts
|

The amino and carboxyl domains of the infectious bronchitis virus nucleocapsid protein interact with 3′ genomic RNA

Abstract: Previous studies indicated that the nucleocapsid (N) protein of infectious bronchitis virus (IBV) interacted with specific sequences in the 3' non-coding region of IBV RNA. In order to identify domains in the N protein that bind to RNA, the whole protein (409 amino acids) and six overlapping fragments were expressed as fusion polypeptides with six histidine-tags. Using gel shift assays, the intact N protein and amino polypeptides, from residues 1 to 171 and residues 1 to 274, and carboxyl polypeptides, extendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Until now, the corresponding protein and its IBV function have not been clear. However, it is hypothesized that the sequences in the IBV 3 -UTR are involved in regulating viral RNA replication and transcription [56]. In addition, Sapats et al [57] reported that shorter forms of the 3 -UTR in the Australian N1/88, Q3/88, and V18/91 strains are associated with a decrease in virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the corresponding protein and its IBV function have not been clear. However, it is hypothesized that the sequences in the IBV 3 -UTR are involved in regulating viral RNA replication and transcription [56]. In addition, Sapats et al [57] reported that shorter forms of the 3 -UTR in the Australian N1/88, Q3/88, and V18/91 strains are associated with a decrease in virulence.…”
Section: Discussionmentioning
confidence: 99%
“…6) (Peng et al, 1995a). Although all these studies consistently attribute a major role in RNA binding to the central portion of the coronaviral N protein, the interaction of the IBV N protein with the 3 0 UTR of IBV RNA mentioned previously was mapped to the amino-and carboxy-terminal domains of the molecule (Zhou and Collisson, 2000). 3 0 UTR RNA-binding activity was also assigned to the amino-terminal domain of the SARS-CoV N protein on the basis of studies using nuclear magnetic resonance spectroscopy (Huang et al, 2004).…”
Section: N-rna Interactionsmentioning
confidence: 95%
“…The RNA-binding capability of the MHV N protein has been mapped to domain 2 of this molecule (Masters, 1992;Nelson and Stohlman, 1993). However, for IBV, two separate RNA-binding sites have been found to map, respectively, to amino-and carboxy-terminal fragments of N protein (Zhou and Collisson, 2000), and RNA-binding activity has been reported for a fragment of the SARS-CoV N protein containing parts of domains 1 and 2 (Huang et al, 2004b).…”
Section: E Nucleocapsid Protein (N)mentioning
confidence: 99%